Human development and mental health: new approaches and metrics needed - Trajano, Julius Cesar Imperial (2022)
The latest UN study reiterated the importance of mental wellbeing and psychological resilience in human development and security. A change in approach and metrics is necessary to improve tackling of mental health issues while simultaneously managing contemporary challenges such as climate change, conflict prevention, and protection of the environment.